2015
DOI: 10.4103/0019-557x.164665
|View full text |Cite
|
Sign up to set email alerts
|

Wealth index and maternal health care: Revisiting NFHS-3

Abstract: The third National Family Health Survey (NFHS-3) is a large dataset on indicators of family welfare, maternal and child health, and nutrition in India. This article using NFHS-3 data is an attempt to bring out the impact of economic status, i.e., the wealth index on maternal health. The study was based on an analysis of the NFHS-3 data. Independent variables taken were the wealth index, literacy, and age at first child birth. Effects of these variables on the maternal health care services were investigated. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
5
3
0
Order By: Relevance
“…Previous studies have shown a linear increase in institutional delivery with an increase in wealth quintiles (Chakraborty, Islam, Chowdhury et al, 2003;Gabrysch and Campbell 2009;Goel, Roy, Rasania et al, 2015;Kesterton, Cleland, Slogett et al, 2010;Titaley, Dibley, and Roberts, 2010;Vora, Mavalankar, Ramani et al, 2009), the present study also showed a similar finding in the case of consistent utilization of institutional delivery. Despite different government incentive programs, the high cost of delivery care is often blamed for the low rate of delivery service utilization, especially for poorer women.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown a linear increase in institutional delivery with an increase in wealth quintiles (Chakraborty, Islam, Chowdhury et al, 2003;Gabrysch and Campbell 2009;Goel, Roy, Rasania et al, 2015;Kesterton, Cleland, Slogett et al, 2010;Titaley, Dibley, and Roberts, 2010;Vora, Mavalankar, Ramani et al, 2009), the present study also showed a similar finding in the case of consistent utilization of institutional delivery. Despite different government incentive programs, the high cost of delivery care is often blamed for the low rate of delivery service utilization, especially for poorer women.…”
Section: Discussionsupporting
confidence: 78%
“…In terms of wealth, the results show that the odds of the mother making 4 or more ANC visits increased as the wealth increased. This result is consistent with the findings of a study by [20] in which it was found that the number of ANC visits increased as the wealth index increased. This finding can be explained by the fact that wealthier women have a higher ability to pay and therefore seek more ANC as compared to those who are poor.…”
Section: Discussionsupporting
confidence: 92%
“…According to the table, women who were in the Poorer, middle, richer and richest wealth quintiles had 30%, 50%, 180% and 640% respectively higher odds of delivering their newborns in a health facility compared to those in the poorest quintile. This result is in line with the finding of [20] in their study of the Wealth Index and Maternal Health Care. The explanation for this is that with higher wealth, the mother is able to have access to health facilities where she can receive proper maternal health care services during delivery from well-trained medical personnel.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations